Frog and toad are friends - Lobel, Arnold (New York : Harper & Row, 1979)
Five tales recounting the adventures of two best friends - Frog and Toad.
"A Harper Trophy I can read book."
"JR20."
Keywords: Frogs -- Juvenile fiction; Toads -- Juvenile fiction; Friendship -- Juvenile fiction